Active Cytomegalovirus Infection in Critically Ill Immunocompeten Patients Admitted in the ICU. A Molecular Diagnosis Approach - Minuljo, Tania Tedjo; Gasem, Muhammad Hussein; Hadi, Purnomo (Journal of Biomedicine and Translational Research, 2017)
Background: Active Cytomegalovirus (CMV) infection has long been related to immunocompromised conditions such as malignancy, HIV-AIDS, longterm use of corticosteroids and organ transplantation. Nowadays, several studies showed that active CMV infection also frequently found in formerly immunocompetent patients during critically ill condition. Alteration of immune system in critically ill condition might become the most possible reason enderlying this adverse event.Aim: To document the prevalence of active CMV infection in critically ill immunocompetent patient admitted to ICU and to find out the difference of the disease severity between group of patients with and without active CMV infection.Method: This was a cross sectional study. Study conducted from April 1st - June 30th 2013. Subjects were patient aged ≥14 years, hospitalized in the ICU of Dr. Kariadi Hospital, Semarang, Indonesia. Patients who had history of malignancy, HIV-AIDS, use of corticosteroids and organ transplatation were excluded from the study. Disease severity was calculated using APACHE II score in the first 24 hours of ICU admission. EDTA sample for qualitative PCR examination (procedure as described elsewhere) collected after 4 days of ICU admission. Primer for CMV were as follow CMV-F: CATGAAGGTCTTTGCCCAGTAC, CMV-R: GGCCAAAGTGTAGGCTACAATAG. Datas were analyzed using bivariate analysis.Result: Active CMV infection was detected in 16 out of 50 subjects. Mean score of disease severity in all subjects (based on APACHE II scoring system) was 11.8±6.43. Mean score of disease severity in group with active CMV infection was higher than group without active CMV infection, but not differ significantly (12.75 vs. 11.47; p=0,510).Conclusion: The prevalence of active CMV infection in critically ill immunocompetent patient is relatively high (16/50; 32%) in the ICU of Dr. Kariadi Hospital, Semarang, Indonesia. Degree of disease severity might influence the occurance of CMV infection. Qualitative PCR testing was an aqurate tool for diagnosing active CMV infection.